2011
DOI: 10.1097/ajp.0b013e31821124a5
|View full text |Cite
|
Sign up to set email alerts
|

Guided Imagery for Musculoskeletal Pain.

Abstract: It is concluded that there are too few rigorous RCTs testing the effectiveness of GI in the management of MSP. Therefore, the evidence that GI alleviates MSP is encouraging but inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 41 publications
0
25
1
Order By: Relevance
“…Also, anxiety reduction has been considered as a possible psychological working mechanism. 21,53,66,79 However, our meta-analysis could not demonstrate an effect of the expectation inductions on anxiety in clinical samples, with the exception of 1 study in which large effects of imagery on anxiety were observed. Preliminary evidence from another study 83 suggests possible effects on pain specific anxiety.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Also, anxiety reduction has been considered as a possible psychological working mechanism. 21,53,66,79 However, our meta-analysis could not demonstrate an effect of the expectation inductions on anxiety in clinical samples, with the exception of 1 study in which large effects of imagery on anxiety were observed. Preliminary evidence from another study 83 suggests possible effects on pain specific anxiety.…”
Section: Discussioncontrasting
confidence: 73%
“…Thus, interventions that can induce analgesic expectations, particularly verbal suggestions for acute procedural pain, were found to relieve patients' pain and can thus possibly be used to optimize the effectiveness of standard analgesic treatments in clinical practice. The findings of this meta-analysis extend previous metaanalyses in which the pain-reducing effects of verbal suggestion and conditioning were studied in the context of placebo effects 80,81 and a meta-analysis and systematic reviews in which the pain-reducing effects of imagery were studied, 66,67,79 by directly comparing the effects of these expectation inductions, while focusing on brief interventions in clinical samples. The observed medium to large effects of verbal suggestion on experimentally evoked and acute procedural pain were generally in line with the findings of a previous meta-analysis 81 and more recent studies in healthy participants, 5,53,76 which supports the transferability of findings from healthy to clinical samples.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…3, 8, 18, 49, 50, 87, 91, 92, 96, 102, 124]. Nonetheless, there are methodological issues with many of the studies conducted in this field, as discussed in recent literature reviews [109, 123]. …”
Section: Neuroimaging Of Mental Imagery In Pain Patientsmentioning
confidence: 99%
“…27 Several of the cognitive-behavioral strategies used as components of CBT have beneficial effects when applied as single strategies, outside of the “therapy” context. For example, relaxation, guided imagery, and distraction strategies have been found to reduce pain 2832 , dyspnea 23,3334 , fatigue 3536 , and sleep disturbance 3739 in various health conditions. Recent research has demonstrated initial efficacy of these strategies across clustered symptoms, including co-occurring pain, fatigue, and sleep disturbance in patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%